Comparison of antioxidant component and capacity in different parts of nutmeg (Myristica fragrans) - Tan, Kim Phing; Khoo, Hock Eng; Azlan, Azrina (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2013)
This study aimed to determine and compare antioxidant components and antioxidant capacity in different parts (skin, pulp, mace and seed) of nutmeg. Freeze dried samples were extracted using 80% methanol, while Folin-Ciocalteu assay was employed to determine total phenolic content, aluminium chloride assay was applied to determine total flavonoid content and ascorbic acid was assessed by titrimetric method. Antioxidant activities were evaluated by ferric reducing antioxidant power and trolox equivalent antioxidant capacity (TEAC) assays. Results revealed that nutmeg seed contained the highest TPC followed by mace, skin and pulp. Similar observation was also found for TFC. The highest ascorbic acid content was found in nutmeg mace, while the lowest was in its pulp. For antioxidant activity, nutmeg seed possessed the highest FRAP and TEAC values, while nutmeg pulp had the lowest as compared to other parts. Phenolic compounds in nutmeg samples have exhibited strong correlation with antioxidant capacity. Therefore, nutmeg is a potential functional food with high antioxidants, especially nutmeg seed. Phenolic compounds in nutmeg samples have exhibited strong correlation with antioxidant capacity. Therefore, nutmeg is a potential functional food with high antioxidants, especially nutmeg seed.